JWST, ALMA, and Keck Spectroscopic Constraints on the UV Luminosity Functions at z ∼ 7–14: Clumpiness and Compactness of the Brightest Galaxies in the Early Universe - Yuichi Harikane; Akio K. Inoue; Richard S. Ellis; Masami Ouchi; Yurina Nakazato; Naoki Yoshida; Yoshiaki Ono; Fengwu Sun; Riku A. Sato; Giovanni Ferrami; Seiji Fujimoto; Nobunari Kashikawa; et al. (The Astrophysical Journal)
We present the number densities and physical properties of the bright galaxies spectroscopically confirmed at z ∼ 7–14. Our sample is composed of 60 galaxies at z _spec ∼ 7–14, including recently confirmed galaxies at z _spec = 12.34–14.18 with JWST, as well as new confirmations at z _spec = 6.583–7.643 with −24 < M _UV < −21 mag using ALMA and Keck. Our JWST/NIRSpec observations have also revealed that very bright galaxy candidates at z ∼ 10–13 identified from ground-based telescope images before JWST are passive galaxies at z ∼ 3–4, emphasizing the necessity of strict screening and spectroscopy in the selection of the brightest galaxies at z > 10. The UV luminosity functions derived from these spectroscopic results are consistent with a double power-law function, showing tensions with theoretical models at the bright end. To understand the origin of the overabundance of bright galaxies, we investigate their morphologies using JWST/NIRCam high-resolution images obtained in various surveys, including PRIMER and COSMOS-Web. We find that ∼70% of the bright galaxies at z ∼ 7 exhibit clumpy morphologies with multiple subcomponents, suggesting merger-induced starburst activity, which is consistent with SED fitting results showing bursty star formation histories. At z ≳ 10, bright galaxies are classified into two types of galaxies: extended ones with weak high-ionization emission lines, and compact ones with strong high-ionization lines including N iv] λ 1486, indicating that at least two different processes (e.g., merger-induced starburst and compact star formation/AGN) are shaping the physical properties of the brightest galaxies at z ≳ 10 and are responsible for their overabundance.